Widma dawnej i nowej historii w powieści sensacyjnej Sławomira Siereckiego "Upiory znikają o brzasku" = Ghosts of old and new history in Sławomir Sierecki`s sensational novel "Upiory znikają o brzasku" [The phantoms fade at dawn] - Ruszczyńska, Marta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article seeks to interpret Sławomir Sierecki`s forgotten novel, "Upiory znikają o brzasku" [The Phantoms Fade At Dawn]. The primary objective was to reconstruct the representation of the Lubuskie Region, focusing specifically on two key locations: Zielona Gora and the palace in Zabor/Danbor. In interpreting the text, research procedures related to popular literature and regionalism were employed, concentrating on the poetics of place.
Keywords: literatura popularna; western; skrajobraz; narracje osadnicze; popular literature; frontier; settlement narratives